AKUISISI BANK ASING TERHADAP PERBANKAN NASIONAL DITINJAU DARI ASPEK HUKUM PERSAINGAN USAHA - Yanuarsi, Susi (Solusi, 2020)
A bank acquisition is carried out by taking over all or part of the shares which results in the transfer of control of the bank to the acquirer. Bank acquisitions can be carried out directly or through the stock exchange. Bank acquisitions can be carried out by Indonesian citizens and / or Indonesian legal entities, as well as by foreign citizens and / or foreign legal entities. The national banking liberalization system has resulted in the acquisition of many Indonesian national private banks by foreign banks which can cause unfair business competition in the world of Indonesian national banking. The positive impact of the acquisition of national private banks by foreign banks, foreign investors provide added value to the national banking system. Banks that acquire national private banks have a competitive advantage in the form of a strong source of funds in foreign exchange, the implementation of sophisticated technology, extensive knowledge of structured finance products, and strong risk management. Meanwhile, the negative impact is the emergence of a gap between the process of accumulating third party funds and the process of channeling them for the benefit of the local and national economy. The lack of participation of foreign banks in funding large-scale business activities in the country, such as funding infrastructure development programs, is due to the very strict risk management calculations they carry out.